The evolution in quality management studies based on the ISO 9001:2015 standard: a bibliometric study - Canal Bravim, Mônica; Shimosakai de Lira, Taisa; Randow de Freitas, Rodrigo; Xavier, Thiago Padovani (Brazilian Journal of Production Engineering, 2020)
The discussion about issues related to Quality Management, such as ISO 9001, has become popular and it is increasingly necessary to follow its evolution and update, given the global importance of the subject. Based on the last revision of the Standard in 2015, considering the need to evaluate the behavior of these studies and the formation of a specific database on the subject, a bibliometric revision was used as a scientific tool. An instrument that allows selection and qualitative and quantitative evaluation of scientific publications within databases (BD). Based on the research and the obtained results, it is confirmed the need for a study based on the ISO 9001: 2015 theme evaluation as a strategic information and direction source for new projects in the academic community, which will work in order to strengthen the theme of quality management. Furthermore, it was possible to visualize and guarantee the importance of the implementation of a Quality Management System, together with a certification, considering more competitive market scenarios, which nowadays require, differentials and an increasing concern with the satisfaction of all its stakeholders.